VD_FINDINFO HC / 2025 / 445 vom 16. Juni 2025 - VD Tribunal cantonal (2025)
OBLIGATION D'ENTRETIEN, EFFET SUSPENSIF, PAIEMENT DE L'ARRIÉRÉ, DOMMAGE IRRÉPARABLE | 315 al. 4 let. b CPC (CH), 315 al. 5 CPC (CH)